A Novel Coagulation Classification and Postoperative Bleeding in Severe Spontaneous Intracerebral Hemorrhage Patients on Antiplatelet Therapy - Liu, Qingyuan; Li, Xiong; Wang, Nuochuan; Yang, Junhua; Wang, Kaiwen; Chen, Shanwen; Li, Jiangan; Wu, Jun; Zhang, Yanan; Wang, Shuo (Frontiers in Aging Neuroscience, 2022)
Background and purpose: For severe spontaneous intracerebral hemorrhage patients on antiplatelet therapy (APT-SICH patients), postoperative rebleeding (PR) is an important cause of poor outcome after surgery. As impacted by coagulation disorder caused by antiplatelet therapy, APT-SICH patients are likely to suffer from PR. This study aimed to assess the risk of PR in APT-SICH patients receiving emergency surgery using a novel coagulation classification. Methods: This prospective, multicenter cohort study consecutively recruited APT-SICH patients between September 2019 and March 2021. The preoperative coagulation factor function was recorded, and the platelet function was assessed using the thrombelastography. Based on platelet and coagulation factor function, a novel four-type coagulation classification, i.e., Type I (severe coagulation disorder), Type IIa (low platelet reserve capacity), Type IIb (normal coagulation) and Type III (hypercoagulation), was presented. The primary outcome was PR, defined as the rebleeding in operative region or new intracerebral hemorrhage correlated with the operation. Results: Of included 197 APT-SICH patients, PR occurred in 40 (20.3%). The novel coagulation classification categorized 28, 32,122 and 15 patients into Type I, Type IIa, Type IIb, and Type III, respectively. The Type I patients had the highest incident rate of PR (39.3 per 100 persons), followed by Type IIa patients (31.3 per 100 persons). In PR-related analysis, the large hematoma volume (hazard ratio, 1.02; 95%CI, 1.02-1.03; p < 0.001), Type I (hazard ratio, 9.72; 95%CI, 1.19-79.67; p = 0.034) and Type IIa (hazard ratio, 8.70; 95%CI, 1.09-69.61; p = 0.041) were correlated with the high risk of PR. The coagulation classification could discriminate the PR patients from NPR patients (p < 0.001), and it outperformed the conventional coagulation assessment (only considering platelet count and coagulation factor function) (c-statistic, 0.72 versus 0.55). Conclusions: The novel coagulation classification could discriminate the APT-SICH patients with high risk of PR preoperatively. For Type I and Type IIa patients, emergency surgery should be careful. Clinical Trial Registration: Chinese Clinical Trial Registry, URL: http://www.chictr.org.cn/index.aspx. Unique identifier: ChiCTR1900024406.